2022
DOI: 10.1002/anie.202115696
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor‐Driven Cascade Reactions Enable the Efficient Preparation of Sugar Nucleotides

Abstract: Glycosylation is catalyzed by glycosyltransferases using sugar nucleotides or occasionally lipid-linked phosphosugars as donors. However, only very few common sugar nucleotides that occur in humans can be obtained readily, while the majority of sugar nucleotides that exist in bacteria, plants, archaea, or viruses cannot be synthesized in sufficient quantities by either enzymatic or chemical synthesis. The limited availability of such rare sugar nucleotides is one of the major obstacles that has greatly hampere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…33−36 Recently, UDP-GlcNAc-derived sugar nucleotides have been succesfully prepared. 37 Here, we aim to synthesize UDP-D-Glc/GDP-D-Man-derived sugar nucleotides from common sugars. The chosen targets are listed in Figure S2, which cover the most reported sugar nucleotides that derive from both common sugar nucleotides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33−36 Recently, UDP-GlcNAc-derived sugar nucleotides have been succesfully prepared. 37 Here, we aim to synthesize UDP-D-Glc/GDP-D-Man-derived sugar nucleotides from common sugars. The chosen targets are listed in Figure S2, which cover the most reported sugar nucleotides that derive from both common sugar nucleotides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As mentioned above, de novo biosynthesis from existing common sugar nucleotides produces the majority of sugar nucleotides in nature. UDP-D-GlcNAc, UDP-D-Glc, and GDP-D-Man are the three most common sugar nucleotides that often convert to other sugar nucleotides in living organisms. Recently, UDP-GlcNAc-derived sugar nucleotides have been succesfully prepared . Here, we aim to synthesize UDP-D-Glc/GDP-D-Man-derived sugar nucleotides from common sugars.…”
Section: Methodsmentioning
confidence: 99%
“…UDP-GlcNAc was prepared from D-GlcNAc as reported previously ( Zheng et al, 2022 ). UDP-Glc and UDP-GlcA were prepared from Sucrose ( Wang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that such cost-effectiveness (and hence viability for multienzyme cascades) had been further improved through regeneration of the required cofactors (NADH, NADPH, NAD + , PMP, and acetyl-CoA, Figure ). , This has recently been exemplified through the synthesis of 25 challenging to access NDP-sugars starting from mannose, sucrose, and N -acetylglucosamine, in high yield, on a multigram scale, and without the need for purifications. , Additionally, the use of polyphosphate kinase (PPK3) or pyruvate kinase (PK) allows for the regeneration of the nucleotide triphosphates using phosphate glass or phosphoenolpyruvic acid (PEP) as sources of phosphate (Figure ). Both methods were effective at regenerating ATP used by sugar kinases and UTP/GTP utilized by NDP-sugar pyrophosphorylases.…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…Recently, it was reported that such cost-effectiveness (and hence viability for multienzyme cascades) had been further improved through regeneration of the required cofactors (NADH, NADPH, NAD + , PMP, and acetyl-CoA, Figure 2 ). 81 , 82 This has recently been exemplified through the synthesis of 25 challenging to access NDP-sugars starting from mannose, sucrose, and N -acetylglucosamine, in high yield, on a multigram scale, and without the need for purifications. 81 , 82 Additionally, the use of polyphosphate kinase (PPK3) or pyruvate kinase (PK) allows for the regeneration of the nucleotide triphosphates using phosphate glass or phosphoenolpyruvic acid (PEP) as sources of phosphate ( Figure 2 ).…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%